2011
DOI: 10.1073/pnas.1112688108
|View full text |Cite
|
Sign up to set email alerts
|

A small pool of vesicles maintains synaptic activity in vivo

Abstract: Chemical synapses contain substantial numbers of neurotransmitter-filled synaptic vesicles, ranging from approximately 100 to many thousands. The vesicles fuse with the plasma membrane to release neurotransmitter and are subsequently reformed and recycled. Stimulation of synapses in vitro generally causes the majority of the synaptic vesicles to release neurotransmitter, leading to the assumption that synapses contain numerous vesicles to sustain transmission during high activity. We tested this assumption by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
110
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 36 publications
(35 reference statements)
13
110
1
1
Order By: Relevance
“…Stimulating synaptic preparations in vitro at physiological frequencies results in the repetitive use of only a fraction of the vesicles (up to ≈20%), termed the recycling pool (1,2). Similarly, we found that living animals only recycled very few vesicles over a few hours (3), which, in contrast to the in vitro situation, constituted only 1-5%. These observations suggest that the bulk of the vesicle population is not involved in recycling at any one time point and therefore may serve another function.…”
contrasting
confidence: 39%
“…Stimulating synaptic preparations in vitro at physiological frequencies results in the repetitive use of only a fraction of the vesicles (up to ≈20%), termed the recycling pool (1,2). Similarly, we found that living animals only recycled very few vesicles over a few hours (3), which, in contrast to the in vitro situation, constituted only 1-5%. These observations suggest that the bulk of the vesicle population is not involved in recycling at any one time point and therefore may serve another function.…”
contrasting
confidence: 39%
“…The pHluorin signal decreases again as endocytosis and vesicle acidification occur. This experimental strategy has revealed the kinetics and retrieval of vesicle dynamics (Granseth et al, 2006), vesicle fusion events in motor neurons in Drosophila larvae (Denker et al, 2011), and endocytosis in situ (Poskanzer, Marek, Sweeney, & Davis, 2003).…”
Section: Subcellular Ph Measurementsmentioning
confidence: 99%
“…• Plasmid encoding a genetically encoded pH biosensor, such as mCherrypHluorin (Denker et al, 2011;Koivusalo et al, 2010) • Polypropylene round-bottom tube, 5 ml (Falcon, catalog number 352063) • Warm media to 37 C in a water bath before use.…”
Section: Materials Requiredmentioning
confidence: 99%
“…One of the most widelyused methods exploits FM-dyes, fluorescent reporters that readily bind to lipid membrane and are taken up into recycling vesicles during endocytosis to provide a functional readout of vesicle turnover [21][22][23] . One dye variant, FM1-43FX, also efficiently drives the polymerization of diaminobenzidine (DAB) when photoactivated, leading to the formation of an osmiophilic precipitate [24][25][26][27][28][29][30][31] . In this way, functional vesicle pools that were previously labelled with FM-dye can be directly identified in electron micrographs.…”
Section: Labelling and Visualizing Functional Vesiclesmentioning
confidence: 99%
“…In this way, functional vesicle pools that were previously labelled with FM-dye can be directly identified in electron micrographs. This approach has been used extensively and highly successfully in cultured neurons 7,10,24,28,30,[32][33][34] , a number of large, peripheral terminals [26][27][28][29]31,[35][36][37] , and large central release sites such as calyx of Held 25 revealing important information about organizational principles of vesicle pools. However, only recently 38 has this method been successfully applied to small central synapses in native brain tissue, where neurons are retained in relevant circuits with defined cytoarchitecture.…”
Section: Labelling and Visualizing Functional Vesiclesmentioning
confidence: 99%